Low Cerebellar Vermis Volumes and Impaired Neuropsychologic Performance in Children Treated for Brain Tumors and Leukemia - Horská, A.; LaClair, A.; Mohamed, M.; Wells, C.T.; McNutt, T.; Cohen, K.J.; Wharam, M.; Mahone, E.M.; Kates, W. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Injury of the cerebellar vermis may occur in children with brain malignancies. Because the vermis is involved in motor and cognitive functioning, the goal of this prospective longitudinal study was to evaluate treatment-related changes in vermal volumes and neuropsychologic performance in children receiving brain radiation of the cerebellum. MATERIALS AND METHODS: Ten patients (mean age, 11.6 years) and 10 healthy children (mean age, 12.1 years) were examined. Lobar vermal volumes and performance on neuropsychologic tests evaluating motor, visual, verbal, attention, memory, and executive functions were assessed at baseline and at 6-month follow-up visits. RESULTS: At baseline, lower mean vermal volumes and impaired performance on visual-spatial and fine-motor tasks were detected in patients. At 6-month follow-up, further decrease in vermal volumes was detected only in patients with medulloblastoma, who received the largest radiation doses to the entire vermis. The volume decrease was not associated with reduction in neuropsychologic performance compared with baseline. At 6-month follow-up, data from all subjects revealed an association between smaller vermal volumes and slower fine-motor speed and lower visual-spatial skills. CONCLUSIONS: Reduced brain-tissue volumes following radiation have been reported previously in pediatric patients. In this study, lower vermal volumes were detected even earlier, before radiation treatment was initiated or completed. Six months postradiation, vermal volume decreases detected in patients with medulloblastoma were not accompanied by declines in already poor neuropsychologic performance. In addition to radiation, the presence of brain malignancies and preradiation treatment may be important factors affecting cerebellar vermis tissue. ALLacute lymphoblastic leukemiaAntanterior vermis, lobules I-VBHboth handsCaPtcarboplatinCPT-IIConner Continuous Performance Test-IICsPtcisplatinCTXcyclophosphamide (Cytoxan)DEXdexamethasoneGLMgeneralized linear modelHChydrocortisoneIC(T-cell) induction chemotherapyICCintraclass correlation coefficientLHleft handMTXmethotrexateη2eta-squaredNPneuropsychologic evaluationNSnonsignificant relationshipPost.posteriorPredprednisonepostVI-VIIposterior vermis, lobules VI-VIIpostVIII-Xposterior vermis, lobules VIII-XRHright handRTradiation therapySSstandard scoresTMZtemozolomideWJ-IIIWoodcock-Johnson IIIVCRvincristineVPventriculoperitonealVP-16etoposide